Regeneration and characterization of Spent Bleaching Clay - Abd. Wafti, Nur Sulihatimarsyila (2006)
The spent bleaching clay (SBC), a solid waste generated from palm oil refinery, may be recycled rather than simply disposed off in landfill. The aim of this study is to investigate the heat regeneration of SBC and to evaluate the performance of the heat-treated SBC on the bleaching of crude oil. The quality of oil is first studied. The quality of the oil extracted from spent bleaching clay from palm oil refinery (SBC-PO) and spent bleaching clay from palm kernel oil refinery (SBC-PKO) much inferior compared to that of crude oil. De-oiling efficiency for both SBC increases as the solid to solvent ratio is decreased.